Distinct neurogenic dynamics of cortico-cortical neuronal subtypes in layer 2/3 of the mouse visual cortex - Major, Mustapha; Pham, Paul; Hernandez-Alvarez, Efrain; Kim, Euiseok J. (Frontiers in Neuroscience, 2025)
In the mammalian cerebral cortex, the birthdates of excitatory projection neurons are closely linked to their laminar positions, which are often associated with distinct long-range projection targets. Although broad relationships between neurogenic timing, laminar position, and projection patterns are well established, the degree to which birthdate specifies projection identity within the same cortical layer remains unclear. In the mouse primary visual cortex (V1), neurons projecting to lateral higher visual areas are relatively evenly distributed throughout layer 2/3, whereas those projecting to medial areas are biased toward more superficial sublayers. To determine whether these projection identities are linked to neurogenic timing, we combined EdU birthdating with retrograde viral tracing. Notably, we found that V1 layer 2/3 neurons projecting to lateral higher visual areas are preferentially born at embryonic day 15.5 (E15.5) compared to E16.5, whereas V1 neurons projecting to medial higher visual areas show no significant birthdate bias between E15.5 and E16.5. These findings suggest that distinct cortico-cortical projection subtypes in layer 2/3 are generated on different temporal schedules, linking neurogenic timing to fine-scale projection identity.